Lessons Learned From the First 10 Consecutive Cases of Intravenous Bacteriophage Therapy to Treat Multidrug-Resistant Bacterial Infections at a Single Center in the United States. (27th August 2020) - Aslam, Saima; Lampley, Elizabeth; Wooten, Darcy; Karris, Maile; Benson, Constance; Strathdee, Steffanie; Schooley, Robert T
Abstract: Background: Due to increasing multidrug-resistant (MDR) infections, there is an interest in assessing the use of bacteriophage therapy (BT) as an antibiotic alternative. After the first successful case of intravenous BT to treat a systemic MDR infection at our institution in 2017, the Center for Innovative Phage Applications and Therapeutics (IPATH) was created at the University of California, San Diego, in June 2018. Methods: We reviewed IPATH consult requests from June 1, 2018, to April 30, 2020, and reviewed the regulatory process of initiating BT on a compassionate basis in the United States. We also reviewed outcomes of the first 10 cases at our center treated with intravenous BT (from April 1, 2017, onwards). Results: Among 785 BT requests to IPATH, BT was administered to 17 of 119 patients in whom it was recommended. One-third of requests were for Pseudomonas aeruginosa, Staphylococcus aureus, and Mycobacterium abscessus . Intravenous BT was safe with a successful outcome in 7/10 antibiotic-recalcitrant infections at our center (6 were before IPATH). BT may be safely self-administered by outpatients, used for infection suppression/prophylaxis, and combined successfully with antibiotics despite antibiotic resistance, and phage resistance may be overcome with new phage(s). Failure occurred in 2 cases despite in vitro phage susceptibility. Conclusions: We demonstrate the safety and feasibility of intravenous BT for a variety of infections and discuss practical considerations that will be critical for informing future clinical trials. Abstract : Bacteriophage therapy (BT) is an emerging therapeutic strategy against multidrug resistant infections. We demonstrate safety and successful outcome in 7/10 cases treated with intravenous BT and share lessons learned, BT referral pattern, and regulatory aspects in the US.